Age-related differences in dual task walking: a cross sectional study - Salamon Kathleen B; Priest Andrew W; Hollman John H (Journal of NeuroEngineering and Rehabilitation, 2008)
Abstract Background Variability in stride velocity during walking characterizes gait instability and predicts falling in older individuals. Walking while executing a cognitive task is also associated with increased risk of falling, particularly in older adults. Variability in stride velocity, particularly during dual task walking conditions, may differ between younger and older individuals. The purpose of this study was to examine whether gait velocity and variability in stride velocity differ between older community-dwelling women and younger women during dual task walking. Methods Twenty-three older (80 ± 9 years) and 19 younger (23 ± 2 years) women walked under each of two conditions: (1) walking at a self-selected velocity and (2) walking at a self-selected velocity while incrementally counting backwards. Gait velocity and variability in stride velocity were measured with GAITRite® instrumentation. Results Gait velocity decreased and variability in stride variability increased, in both groups, during dual task walking. The relative reduction in gait velocity and the magnitude of variability in stride velocity were greater in the older subjects than younger subjects. Conclusion The gait changes observed in dual task walking characterize reduced gait stability and indicate that cognitively demanding tasks during walking have a destabilizing effect on gait that may place older persons at greater risk of falls.